2012
DOI: 10.1242/jeb.060889
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of behaviorally associated gene networks in worker honey bee ovaries

Abstract: Fat body expression of hormone receptor-like in 46 (HR46) and phosphoinositide-dependent kinase-1 (PDK1) correlates with ovary size as well as worker division of labor (Wang et al., 2009). HR46 is a possible nuclear hormone receptor for ecdysteroid hormones Accepted 28 September 2011 SUMMARY Several lines of evidence support genetic links between ovary size and division of labor in worker honey bees. However, it is largely unknown how ovaries influence behavior. To address this question, we first performed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 91 publications
1
57
1
Order By: Relevance
“…Our challenge is to understand how those remote signals are integrated. Recent work suggests that tissues as diverse as brain and ovary are regulated by the same systemic factors such as JH, ecdysteroids and Vg that form a global network that modulates individual behavior (Wang et al, 2012a;Wang et al, 2012b). Our findings suggest that microRNAs can be part of this network, potentially acting both within tissues as local signals and between tissues as remote signals.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our challenge is to understand how those remote signals are integrated. Recent work suggests that tissues as diverse as brain and ovary are regulated by the same systemic factors such as JH, ecdysteroids and Vg that form a global network that modulates individual behavior (Wang et al, 2012a;Wang et al, 2012b). Our findings suggest that microRNAs can be part of this network, potentially acting both within tissues as local signals and between tissues as remote signals.…”
Section: Discussionmentioning
confidence: 68%
“…New evidence makes it increasingly likely that ecdysteroids influence honey bee social behaviors (Velarde et al, 2009;Wang et al, 2009;Wang et al, 2012b), and we have identified microRNAs Table S1 for definitions and information on the gene symbols.…”
Section: Microrna Target Prediction In Genes Associated With Foragingmentioning
confidence: 99%
“…Here, we were able to use a one-tailed test for TYR1 because we had a priori expectations of a reduction in TYR1 expression in the bees that experienced starvation during development. Previously, we found that the bees with fewer ovarioles had less TYR1 mRNA (Wang et al, 2012b; Y.W., G.V.A. and R.E.P., unpublished data).…”
Section: Fat Body Gene Expression Associated With Early Food Deprivationmentioning
confidence: 67%
“…We used a one-tailed test for TYR1. We expected a priori TYR1 down-regulation because of a consistent correlation between ovariole number and TYR1 mRNA levels in other studies (Wang et al, 2012b; Y.W., G.V.A. and R.E.P., unpublished data).…”
Section: Statisticsmentioning
confidence: 69%
See 1 more Smart Citation